Dynamics fingerprint and inherent asymmetric flexibility of a cold-adapted homodimeric enzyme. A case study of the Vibrio alkaline phosphatase - Papaleo, Elena; Renzetti, Giulia; Invernizzi, Gaetano; Ásgeirsson, Bjarni (Biochimica et biophysica acta, 2013)
Protein dynamics influence protein function and stability and modulate conformational changes. Such motions depend on the underlying networks of intramolecular interactions and communicating residues within the protein structure. Here, we provide the first characterization of the dynamic fingerprint of the dimeric alkaline phosphatase (AP) from the cold-adapted Vibrio strain G15-21 (VAP), which is among the APs with the highest known kcat at low temperatures. Multiple all-atom explicit solvent molecular dynamics simulations were employed in conjunction with different metrics to analyze the dynamical patterns and the paths of intra- and intermolecular communication. Interactions and coupled motions at the interface between the two VAP subunits have been characterized, along with the networks of intramolecular interactions. It turns out a low number of intermolecular interactions and coupled motions, which result differently distributed in the two monomers. The paths of long-range communication mediated from the catalytic residues to distal sites were also characterized, pointing out a different information flow in the two subunits. A pattern of asymmetric flexibility is evident in the two identical subunits of the VAP dimer that is intimately linked to a different distribution of intra- and intermolecular interactions. The asymmetry was also evident in pairs of cross-correlated residues during the dynamics. The results here discussed provide a structural rationale to the half-of-site mechanism previously proposed for VAP and other APs, as well as a general framework to characterize asymmetric dynamics in homomeric enzymes. ► Dimeric enzyme dynamics and underlying intra- and intermolecular interaction networks. ► Asymmetric flexibility. ► Different paths of long-range communication in the individual subunits.